2015
DOI: 10.1002/anie.201411509
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Subtle Energy Balance in Protic Ionic Liquids: Dispersion Forces Compete with Hydrogen Bonds

Abstract: The properties of ionic liquids are determined by the energy-balance between Coulomb-interaction, hydrogen-bonding, and dispersion forces. Out of a set of protic ionic liquids (PILs), including trialkylammonium cations and methylsulfonate and triflate anions we could detect the transfer from hydrogen-bonding to dispersion-dominated interaction between cation and anion in the PIL [(C6 H13 )3 NH][CF3 SO3 ]. The characteristic vibrational features for both ion-pair species can be detected and assigned in the far-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 26 publications
11
96
2
Order By: Relevance
“…2,3 A significant contribution is also supposed to arise from a three-dimensional network of hydrogen bonds between the counterions 4,5 as well as from dispersion interactions. 8,9 Apart from the binding energy perspective, a comprehensive understanding of the complete pattern of non-covalent interactions between the constituting ions and the related electron density distribution is a key prerequisite for consistent IL characterization. These weak non-covalent interactions can contribute up to 20 percent of the overall interaction energy in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 A significant contribution is also supposed to arise from a three-dimensional network of hydrogen bonds between the counterions 4,5 as well as from dispersion interactions. 8,9 Apart from the binding energy perspective, a comprehensive understanding of the complete pattern of non-covalent interactions between the constituting ions and the related electron density distribution is a key prerequisite for consistent IL characterization. These weak non-covalent interactions can contribute up to 20 percent of the overall interaction energy in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…A significant portion (if not all) of the 43−50% ion-pairing character is expected to involve the bicarbonate anion associated with the ammonium cation through a hydrogen bond, which is consistent with other protic ionic liquids (PIL). 32 Previously published data from our lab identified that, when the carbonate anion is not associated, there is likely a tightly bonded hydration environment. 18,33 It was suggested that this hydration sphere required a steric environment which is supported by significant steric impacts on entropic stability of BH + ·H 2 O complexes.…”
Section: Articlementioning
confidence: 95%
“…Therefore, the interaction energy is not determined by H-bond interaction or Van der Waals interaction individually but by the combined effect of those two interactions. As a rule, the considerable effect of Van der Waals interaction results from the ethyl chains in cation [47].…”
Section: Interaction Energiesmentioning
confidence: 99%